The association between serum prolactin levels and interleukin-6 and systemic lupus erythematosus activity - W.A. Wan Asyraf; M.S. Mohd Shahrir; W. Asrul; A.W. Norasyikin; O. Hanita; W.Y. Kong; M.T. Azmi (PAGEPress Publications, 2018)
Based on the recent evidence of association between hyperprolactinemia and systemic lupus erythematosus disease activity (SLEDAI), a study was conducted to analyze the association of hyperprolactinemia with lupus nephritis disease activity. In this cross-sectional study, the analysis was conducted on SLE patients who visited the University Kebangsaan Malaysia Medical Centre (UKMMC) Nephrology Clinic from August 2015 till February 2016. The disease activity was measured using the SLEDAI score, with more than 4 indicating active lupus nephritis. Basal resting prolactin level was analyzed in 43 patients with lupus nephritis, in 27.9% of them had raised serum prolactin. The median of serum prolactin level at 0 minutes was 19.91 ng/mL (IQR: 15.95-22.65 ng/ mL) for active lupus nephritis, which was significantly higher compared to the median of serum prolactin level of 14.34 ng/mL (IQR: 11.09-18.70 ng/mL) for patients in remission (p=0.014). The serum prolactin level positively correlated with SLEDAI (rhos: 0.449, p=0.003) and the UPCI level in lupus nephritis patients (rhos: 0.241, p=0.032). The results were reproduced when the serum prolactin was repeated after 30 minutes. However, the serum prolactin levels at 0 minutes were higher than those taken after 30 minutes (p=0.001). An assessment of serum IL-6 levels found that the active lupus nephritis patients had a higher median level of 65.91 pg/ mL (IQR: 21.96-146.14 pg/mL) compared to the in-remission level of 15.84 pg/mL (IQR: 8.38-92.84 pg/mL), (p=0.039). Further correlation analysis revealed that there was no statistical correlation between the interleukin (IL)-6 levels with serum prolactin, SLEDAI and other lupus nephritis parameters. An ROC curve analysis of serum prolactin at 0 minutes and serum prolactin after 30 minutes and IL-6 levels for prediction of SLE disease activity provided the cutoff value of serum prolactin at 0 minutes, which was 14.63 ng/mL with a sensitivity of 91.7% and specificity of 58.1% and AUC of 0.74 (p=0.015). This study concurred with the previous findings that stated that hyperprolactinemia is prevalent in SLE patients and correlated with clinical disease activity and UPCI level. The baseline of the fasting serum prolactin level was found to be a sensitive biomarker for the evaluation of lupus nephritis disease activity.